A Teaching Note on Unconscionable and Adhesive Contracts - Hunter, Richard J.; Shannon, John H.; Amoroso, Henry J.; Lozada, Hector R. (Archives of Business Research, 2023)
In this article, the authors, professors of legal studies, joined by a colleague from the discipline of marketing, write about the topic of unconscionability as it relates to the common law doctrines of “freedom of contract,” caveat emptor, and contracts of adhesion. Unconscionability can be a “threshold” discussion, or it can be considered at another point in a business law or legal environment of business course under the topic of “genuineness of assent.”